Three-Dimensional TID Hardening Design for 14 nm Node SOI FinFETs - Peng Lu; Can Yang; Yifei Li; Bo Li; Zhengsheng Han (Eng, 2021)
The fin field-effect transistor (FinFET) has been the mainstream technology on the VLSI platform since the 22 nm node. The silicon-on-insulator (SOI) FinFET, featuring low power consumption, superior computational power and high single-event effect (SEE) resistance, shows advantages in integrated circuits for space applications. In this work, a rad-hard design methodology for SOI FinFETs is shown to improve the devices’ tolerance against the Total Ionizing Dose (TID) effect. Since the fin height direction enables a new dimension for design optimization, a 3D Source/Drain (S/D) design combined with a gate dielectric de-footing technique, which has been readily developed for the 14 nm node FinFETs, is proposed as an effective method for SOI FinFETs’ TID hardening. More importantly, the governing mechanism is thoroughly investigated using fully calibrated technology computer-aided design (TCAD) simulations to guide design optimizations. The analysis demonstrates that the 3D rad-hard design can modulate the leakage path in 14 nm node n-type SOI FinFETs, effectively suppress the transistors’ sensitivity to the TID charge and reduce the threshold voltage shift by >2×. Furthermore, the rad-hard design can reduce the electric field in the BOX region and lower its charge capture rate under radiation, further improving the transistor’s robustness.